New Vox in Poetic Inquiry: Rhizomatic Runners in a Fruiting Field - Borhani, Maya T. (Art/Research International)

(untitled) (University of Alberta, 2021)
As a doctoral candidate ever-deepening my understandings of arts-based research methods, in general, and performative and poetic methods of inquiry in particular, this paper advances several new theories of Vox in poetic inquiry (Prendergast, 2009, 2015, 2020), playing with the generative possibilities found with/in such poeticizing as writing method, performative gesture, and reflexive praxis, while addressing intersections between the personal/public and poetry as political currency. Woven as a métissage of poetic offerings within theoretical exposition, this essay links theory, research methods, and personal explorations with/in poetic inquiry. Found poems and original compositions punctuate the proposal of several new Vox to help elucidate our myriad voices within a growing chorus of poetic inquirers singing to a variety of purposes. A journey through methodological praxis unfolds, poses further questions, and encourages ongoing exploration and practice of poetic research methodologies in diverse, rhizomatically fruiting tendrils and directions.